Measuring the constructs of health literacy in the Iranian adult Kurdish population - Arezoo Yari; Marzieh Soofimajidpoor; Ghobad Moradi; Farzam Bidarpoor; Haidar Nadrian; Abedin Iranpoor; Mehdi Zokaie; Daem Raoshani; Nahid Ghotbi; Yadolah Zarezadeh (BMC, 2021)
Abstract Background Health literacy is essential to self-care, which is an important precedence to improve the quality of healthcare services and a key factor in health. It also plays a pivotal role in decision-making in various health fields. Therefore, policymakers consider health literacy to be a primary tool to promote community health and enhance the proper use of healthcare services. The present study aimed to assess the health literacy status of the Kurdish population in Kurdistan province, Iran based on the nine constructs of the Iranian health literacy questionnaire (IHLQ) individually and collectively and determine the significant effects of demographic variables on health literacy. Methods This cross-sectional study was conducted on the Iranian adult Kurdish population living in the urban and rural areas of Kurdistan province, willing to participate during April 2017-September 2018. Data were collected using the IHLQ. The sample size was determined to be 980 people, with 490 in the rural areas and 490 in the urban areas. The researchers visited potential participants at their doorstep, asking them to complete the questionnaire. The willing participants were assisted in completing the IHLQ in case they were illiterate; the questions and answers were read by the researchers to the participants, and the responses were recorded. Results About 50.4% (n = 494) of the Kurdish population had poor health literacy, while 34.0% (n = 333) had average health literacy, and 15.6% (n = 153) had good health literacy. Meanwhile, 60.2% of the participants obtained poor scores in the construct of health information access, and 74.1% (n = 726) obtained poor scores in the individual empowerment construct. In addition, the analysis of the adjusted model indicated that education level (lowest β = 7.42; P = 0.001) and in male participants (β = − 1.10; P = 0.001) were significantly associated with higher health literacy. Conclusion According to the results, the investigated Kurdish population mostly had average or low health literacy. Therefore, proper strategies should be adopted to enhance the health literacy of this population and increase their access to health information. Furthermore, effective training should be provided to these individuals (especially vulnerable social groups) to improve their individual capabilities to compensate for poor health literacy.